An advocacy campaign on strengthening the mass movement for free public education up to tertiary level in the Philippines - Cruz, Clarissa I.; Viriña, Conrado (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
They say that if you can dream it, you can do it. Since we were kids, we were taught to dream and how vital education is in achieving those dreams. We'd be asked questions such as "after you finish your studies, what do you want to be?" We respond by saying that we want to be a pilot, a teacher, an astronaut or whatever we can think of, as if all of it is possible or that we can actually be whatever we want to be. But as we grow up, we begin to see reality and understand how that's not actually the case. We realize that it's not easy to get a college degree; it's not easy to reach your dreams. That is the case for the majority or more than 90% of Filipinos who come from families with low income, or the people we identify as the basic masses. According to data from CHED, 1 in every 10 or about 4 million Filipino children and youth ages 6-25 years old are out-of-school and 9.3% of Filipinos aged 6 and over or about 7.6 million reach college but are not able to graduate, wherein the top reasons for this include the high cost of education and their family's inability to sustain it because of low income. Why is education important? One of the most imporatant reasons is that it is an individual's right, a right that is essential for the practice all our other rights. Another aspects is that it is a powerful tool wherein socially and economically marginalized individuals can lift themselves out of poverty and can then participate fully as citizens for a sustainable development of a country. In the Philippines, there have already been many attempts to make public education free up the tertiary level. One example is the House Bill 4800 or the Comprehensive Free Public Higher Education Act that has been propsed in the Senate last January 2017. However, the government is giving priority to lowering the age of criminalizing or in other words, the government is willing to allocate budget on punishing children of the Philippines rather than giving them education. According to the documents from Kabataan Partylist, the organization that structured the propsed HB4800, having free education uo to the tertiary level is feasible in the Philippines, and is possible if the government opts to prioritize allocating budget for it. Now, the question is what can a simple Filipino citizen do to help fix this situation. The key is that, one of the most basic, accessible and powerful way is to join the mass movement for free education in the Philippines because through this, we show solidarity as citizens of this country and pressure the government into prioritizing this issue. There is an ongoing mass movement for free education up to tertiary level in the Philippines, just as there are ongoing mass movements for education throughout the world. One example is the recent fees must fail in South Africa, which has already won in their call to stop the tuition fee hikes last 2016, and the ongoing million students march in the United States. This thesis tackles the reason behind this current situation of education in the Philippines and a campaign to get the Filipino youth to join the mass movement for free education up to the tertiary level in the Philippines.
Thesis (Bachelor of Fine Arts major in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 49-50.
Keywords: Education, Higher -- Law and legislation -- Philippines; Education, Higher